How Hiring Agricultural Managers Affect Farmland Quality Protection Behavior in Farmers’ Cooperatives—Evidence Based on the Survey of Cooperatives in Sichuan, China - Guo-Yan Zeng; Jie-Hao Deng; She-Mei Zhang (Land)
This paper aims to include the human capital elements of agricultural managers in the decision-making process of farmland quality protection behavior in farmers’ cooperatives in an effort to discuss and explore the relationship between hiring agricultural managers and the implementation of farmland quality protection behavior. Based on the survey questionnaire of 436 planting cooperatives in Sichuan, China, in 2021, the Poisson model and mediating effect model were used to explore the impact and mechanism of hiring agricultural managers on farmland quality protection behavior in farmers’ cooperatives. The empirical results reveal that hiring agricultural managers significantly elevates farmland quality protection behavior in farmers’ cooperatives. Compared to cross-period farmland quality protection behavior, hiring agricultural managers has a greater impact on single-period farmland quality protection behavior. Through the improvement of information technology application level, the farmland quality protection behavior in cooperatives can be elevated by hiring agricultural managers, but standardized management has a masking effect between the two. Accordingly, continuous development and growth of the agricultural manager team encourages cooperatives to establish a standardized system for recruiting farm managers and strengthen the link between farm managers and cooperatives. The training of agricultural managers should be optimized to deepen their mastery of techniques and knowledge and protect the quality of arable land. Material and moral incentives should be provided to encourage farm managers to focus on the long-term development of their cooperatives. The government should be encouraged to establish a platform for sharing information on farmland quality to provide technical support to farm managers to carry out targeted work on farmland quality protection.